Cytotoxic constituents of Clausena excavata - Mohd Shariff, Nurul Waznah; Mustahil, Noorul Adawiyah; Mohd Noor, Halimatul Saadiah; Md. Sukari, Mohd Aspollah; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Ee, Gwendoline Cheng Lian (Academic Journals, 2011)
Phytochemical investigation on leaves, stem bark and roots of Malaysian Clausena excavata has led to the isolation and identification of limonoid compounds, clausenolide-1-methyl ether (1) and clausenarin (2), carbazole alkaloids, 3-formyl-2,7-dimethoxycarbazole (3) and clausine-K (4) together with coumarins, xanthyletin (5), dentatin (6) and nordentatin (7). Extracts of roots and isolated compounds (1), (2), (5) and (6) were subjected to cytotoxic screening against various cancer cell lines (HL-60, MCF- 7, HeLa and HT-29). All roots extracts except methanol showed strong activity against HL-60 and MCF-7 cancer cell lines with IC 50 values ranging from 4 to 6 μg/ml. Dentatin (6) was found to be the most cytotoxic constituent against all cancer cell lines with IC50 values ranging from 5 to 10 μg/ml.